Latent heat must be visible in climate communications. (14th April 2022) - Matthews, Tom; Byrne, Michael; Horton, Radley; Murphy, Conor; Pielke, Roger; Raymond, Colin; Thorne, Peter; Wilby, Robert L.
Abstract: Anthropogenic forcing is driving energy accumulation in the Earth system, including increases in the sensible heat content of the atmosphere, as measured by dry‐bulb temperature—the metric that is almost universally used for communications about climate change. The atmosphere is also moistening, though, representing an accumulation of latent heat, which is partly concealed by dry‐bulb temperature trends. We highlight that, consistent with basic theory, latent heat gains are outpacing sensible heat gains over about half of the Earth's surface. The difference is largest in the tropics, where global "hotspots" of total heat accumulation are located, and where regional disparities in heating rates are very poorly represented by dry‐bulb temperatures. Including latent heat in climate‐change metrics captures this heat accumulation and therefore improves adaptation‐relevant understanding of the extreme humid heat and precipitation hazards that threaten these latitudes so acutely. For example, irrigation can lower peak dry‐bulb temperatures, but amplify latent heat content by a larger margin, intensifying dangerous heat stress. Based on a review of the research literature, our Perspective therefore calls for routine use of equivalent temperature, a measure that expresses the combined sensible and latent heat content of the atmosphere in the familiar units of °C or K. We recognize that dry‐bulb air temperature must remain a key indicator of the atmospheric state, not least for the many sectors that are sensitive to sensible heat transfer. However, we assert here that more widespread use of equivalent temperature could improve process understanding, public messaging, and adaptation to climate change. This article is categorized under: Assessing Impacts of Climate Change > Observed Impacts of Climate Change Paleoclimates and Current Trends > Earth System Behavior Abstract : Air temperature trends (left) identify regions accumulating sensible heat fastest under climate change, for example the Arctic (Svalbard). However, total heat gains (sensible and latent) are revealed by trends in equivalent temperature (right). Analysis with this metric identifies that some subtropical regions, such as the Indus Valley in Pakistan, are global hotspots of heat accumulation.